2003
DOI: 10.1097/01.lab.0000097190.56734.fe
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Activates Nuclear Factor-KappaB through Toll-Like Receptors and Related Molecules in Cultured Biliary Epithelial Cells

Abstract: SUMMARY:To clarify the innate immunity of the intrahepatic biliary tree, we examined expression of Toll-like receptors and intracellular signalings in biliary epithelial cells in response to bacterial components by using cultured biliary epithelial cells (murine biliary cells and human cholangiocarcinoma cell lines). The expression of Toll-like receptors in cultured cells was examined by reverse transcription and PCR and immunohistochemistry. Intracellular signalings after Toll-like receptors activation by lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 144 publications
(156 citation statements)
references
References 39 publications
(65 reference statements)
5
150
1
Order By: Relevance
“…14,17,18,29,30 In the TLR family, TLR3 recognizes dsRNA and is located in the endosomal membranes with the ligand-binding domain facing the lumen of the endosomes and the signaling domain positioned on the cytoplasmic side. Therefore, TLR3 allows cells to detect dsRNA that is phagocytosed from the extracellular space, where it is released by infected cells that are undergoing lysis or necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,17,18,29,30 In the TLR family, TLR3 recognizes dsRNA and is located in the endosomal membranes with the ligand-binding domain facing the lumen of the endosomes and the signaling domain positioned on the cytoplasmic side. Therefore, TLR3 allows cells to detect dsRNA that is phagocytosed from the extracellular space, where it is released by infected cells that are undergoing lysis or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…For the evaluation of messenger ribonucleic acid (mRNAs) of TLR3, RIG-I, MDA-5, PKR, NF-B, interferon regulatory factor-3 (IRF-3), IFN-␤, MxA, TRAIL, TRAIL receptors (TRAIL-DR4, TRAIL-DR5, TRAIL-DcR1, and TRAIL-DcR2), CD95, and CD95 ligand in cultured BECs, total RNA was isolated from BECs, and 1 g total RNA was reverse-transcribed with an oligo-(dT) primer and reverse transcriptase to synthesize complementary deoxyribonucleic acid. Human cultured cell lines (HuCCT1, HuH7, HepG2, and WI38) and normal tissues (pancreas and liver) [18][19][20][21][22][23][24][25][26][27] were used as controls, and the complementary deoxyribonucleic acid was amplified by polymerase chain reaction (PCR) using the specific primers ( Table 1). The PCR products were subjected to electrophoresis on 1.5% agarose gels containing ethidium bromide.…”
Section: Patients and Tissue Preparationsmentioning
confidence: 99%
“…In addition, it has been reported that bacterial components (e.g., intestinal lipopolysaccharides) may stimulate macrophages to produce enough TGF-β from those cells, resulting in induction of severe fibrosis (29). It seems likely, because biliary epithelial cells constantly express at least Toll-like receptors 2-5 and can respond to the Toll-like receptor ligands (lipopolysaccharides) derived from the duodenum (30). In addition, it has been pointed out that IL-17A promotes the development of several autoimmune diseases as one of the factors (31).…”
Section: Discussionmentioning
confidence: 99%
“…64,65 TLR2, 3, 4 and 5, but not TLR7, 8,9, were detected at the protein level and appeared functionally active based on ligand-induced IL-6, IL-8 and MCP-1 production in biliary epithelial cell lines. 66,67 In vitro TLR mRNA expression and, to a lesser extent, protein levels were increased by Th1 cytokines (IFN␥ and TNF␣) in biliary cells. 66,67 In vivo, however, LPS failed to elicit an inflammatory response in intrahepatic cholangiocytes.…”
Section: Prrs In Liver Diseasesmentioning
confidence: 99%